(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
Relevance of the topic : It is not a secret to anyone that rapid reclamation of lands, that is, their increasing salinity and reduction of irrigation water reserves will turn Uzbekistan into the most difficult region of the arid region in the coming years. Now it is considered appropriate to carry out large-scale practical and scientific researches on improving soil reclamation and saving irrigation water reserves in agriculture of the Republic (4,5,10). During the visit of the President of the Republic of Uzbekistan to the Syrdarya region in May 2017 and April 2018, the factory "Bek cluster" was established, where it is planned to grow 80 thousand tons of food crops. Cultivation of fodder crops in the conditions of the Syrdarya region is an urgent issue for the implementation of the above-mentioned specific task (1).The purpose and objectives of the study: Salinity resistance of the "Qorabosh" variety of sorghum (sorghum) grown on salted lands, salt washing and irrigation procedures, the effect of sorghum growth, yield and product quality are studied. Object of the research: The research was conducted at the farm "Bekzafarlik Khorvadoril" of Babur WUU in the direction of animal husbandry in Oq Oltin District, Syrdarya Region. The soil of the experimental area is meadow-sierozem. The field experiment was conducted in 9 variants, 4 repetitions. The options are arranged in one tier. The length of the rows is 50 m. Each option includes 8 rows, i.e. one return of the seeder (50X5.6-280 m2). The total area of each plot is 280 m2, the accounted area is 140 m2. Based on this, the total area of the experiment was 10080 m2, and the calculated area was 5040 m2.